117 Management of Spinal Accessory Nerve Palsy. (28th February 2022) - Rupra, R.; Malone, P.; Power, D.; Chaudhry, T.
Abstract: Aim: To discuss our strategies employed in our peripheral nerve injury unit for spinal accessory nerve (SAN) injury and a potential algorithm for future use. Method: A retrospective analysis was undertaken on 9 patients with SAN injury undergoing surgical intervention. Neurophysiological results were obtained. MRC grades were compared at presentation and post-operatively. DASH (Disability of the arm, shoulder, and hand) scores were also collected post-operatively. Results: 7 patients presented to us following an iatrogenic injury to the SAN. 6 patients underwent neurolysis only, 3 underwent nerve transfer, 2 underwent nerve grafting (1 autologous, 1 processed nerve allograft). The mean time frame from presentation to operation was 13 months. MRC grading of shoulder function increased from a mean MRC 2 to 4 at a mean of 8 months post-operatively. DASH scores of the 7 participating patients were 30.8 at a mean of 47 months post-operatively. 2 patients had experienced a sensory deficit. Conclusions: Nerve grafting allows bridging of a gap when the injury is well defined with a suitable window for re-innervation. Allograft has a role in small gaps where there may be concerns with autograft. Nerve transfer may allow earlier re-innervation and be a more reliable option where the proximal extent of nerve injury is poorly defined. We found nerve wraps to be a useful addition when an injured nerve may be adherent to a heavily scarred bed. We will present some worked examples along with a potential algorithm for a surgical strategy.